2017
DOI: 10.1007/s11277-017-4158-7
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Validation of a Compact Planar Butler Matrix by Removing Crossover

Abstract: In this work a compact planar butler matrix is presented by removing the 0 dB crossover. The proposed butler matrix consists of 45°and 90°phase shifter, and four branch line coupler miniaturised by employing open stubs in each transmission line. As the crossover is removed from the circuit, the circuit size is reduced and the performance is enhanced compared to the conventional Butler matrix. The response obtained from the newly designed butler matrix is comparable to the conventional butler matrix which is op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In order to maintain small BM dimensions, the crossover used here departs from the standard designs composed as a cascade connection of hybrid couplers [ 28 , 29 , 33 ]. Instead, it is based on a microstrip-to-coplanar-waveguide (CPW) transition.…”
Section: Numerical Results and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to maintain small BM dimensions, the crossover used here departs from the standard designs composed as a cascade connection of hybrid couplers [ 28 , 29 , 33 ]. Instead, it is based on a microstrip-to-coplanar-waveguide (CPW) transition.…”
Section: Numerical Results and Experimentsmentioning
confidence: 99%
“…In recent years, the design of Butler matrices for space-limited applications has gained significant attention of the research community [16,[25][26][27][28][29][30][31][32][33]. Popular miniaturization techniques are oriented toward replacing BM building blocks with their miniaturized counterparts [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…The main beam of an antenna is steered by the BFN network with the given phase and amplitude. There are many different types of BFNs reported in the literature [9]- [14], [16]- [18], [22]- [27]. The BFNs have two categories 1) Rotman lens and 2) Circuit-based beamformer.…”
Section: Introductionmentioning
confidence: 99%
“…In [16], it is shown that the use of 45 • and 90 • phase shifters and four BLCs miniaturized by employing open-stubs in each transmission-line allows the size reduction of 42.68% as compared to the conventional BM. In [11], a miniaturized BM using cross-slot patch hybrid couplers and 45 • phase shifters using short-circuited stubs are presented.…”
Section: Introductionmentioning
confidence: 99%
“…The design of miniaturised BMs has recently gained the attention of the research community [2][3][4][5][6][7]. Popular size reduction techniques include replacement of the BM building blocks by their compact counterparts [3,4], implementation of the structures on multi-layer substrates [5], or development of BMs without some of the components [6,7]. Application of the mentioned techniques allows for obtaining between 60% to 85% miniaturisation.…”
mentioning
confidence: 99%